Design of mm-wave Front-end for Multiantenna Communication Systems - Zhou, Han (My University, 2018)
A Ka-band (desired frequency band: 27.5 GHz − 32.5 GHz) receiver front-end is de- signed in a 130 nm BiCMOS process. A triple balanced capacitive mixer with varac- tor diodes is demonstrated and it achieves an IIP3 of 45 dBm, with a conversion loss of 20 dB. In order to support the proposed mixer, an inductive emitter-degenerated cascode LNA cascaded with a differential pair active balun is proposed. The LNA has a reflection coefficient of less than -20 dB, an available gain of more than 17 dB, a noise figure of less than 2.4 dB, an IIP3 of 10 dBm and a power consumption of 12 mW. The active balun has a maximum phase error of 0.5◦ and an amplitude imbal- ance of 40 mdB. In addition, self biasing and bandgap reference circuits are studied and simulated. Finally, a layout prototype of the receiver front-end is presented, with a total area of 0.9 mm×0.7 mm.
Keywords: Informations- och kommunikationsteknik; Innovation och entreprenörskap (nyttiggörande); Data- och informationsvetenskap; Elektroteknik och elektronik; Kommunikationssystem; Information & Communication Technology; Innovation & Entrepreneurship; Computer and Information Science; Electrical Engineering, Electronic Engineering, Information Engineering; Communication Systems